A 7.5 kW Off-board Three-Phase Fast Charger Prototype for Electric Vehicles - Suarez, Camilo A. [UNESP]; Melo, Guilherme A. [UNESP]; Canesin, Carlos A. [UNESP] (My University, 2018)
This paper describes the implementation of a7.5 kW off-board Electric Vehicle (EV) fast charger prototype. It is composed by a three-phase hybrid rectifier with power factor correction (AC/DC stage), followed by an interleaved buck converter (DC/DC stage). At AC/DC stage, sinusoidal input phase currents are imposed, and consequently low Total Harmonic Distortion (THD) is obtained by the use of Zero Current Switching (ZCS) SEPIC rectifiers when applying a simple hysteresis control. These converters manage a fraction of the total power delivered by the hybrid rectifier, reducing the semiconductors current stress and allowing the use of this topology for high power levels. The interleaved buck converter is controlled by Pulse Width Modulation (PWM), allowing Constant Current - Constant Voltage (CCCV) charging technique, typically used in Lithium-ion (Li) batteries and Supercapacitors (SC).
Keywords: Battery charger; Interleaved converters; Power converters for EV; ZCS converters